Surprise and design creativity: investigating the drivers of unexpectedness. Issue 1 (3rd April 2017) - Becattini, N.; Borgianni, Y.; Cascini, G.; Rotini, F.
Abstract: Scholars argue about the role played by surprise in making new products creative. Different perspectives evaluate surprise as a nuance of novelty, an independent dimension, or an emotional reaction to new products. The paper proposes a framework of factors supposedly characterizing the emergence of surprise in terms of individuals' interpretations and/or modifications of products' behavior and structure. Moreover, it illustrates the outcomes of a preliminary empirical investigation about the manifestation of unexpectedness according to such a framework: the proposed factors have been checked by interpreting the motivations leading to the presence of surprise in 12 new lamps described in the literature. The experiment states the reasonability of the described factors and, as a consequence, the paper provides a contribution to better articulate the debate in the research arena.